Severe Recurrent Bacterial Pneumonia Among Children Living With HIV. Issue 5 (18th February 2022) - Boettiger, David C.; An, Vu Thien; Lumbiganon, Pagakrong; Wittawatmongkol, Orasri; Huu Truong, Khanh; Chau Do, Viet; Van Nguyen, Lam; Sun Ly, Penh; Kinikar, Aarti; Ounchanum, Pradthana; Puthanakit, Thanyawee; Kurniati, Nia; et al.
Abstract : Background: Bacterial pneumonia imparts a major morbidity and mortality burden on children living with HIV, yet effective prevention and treatment options are underutilized. We explored clinical factors associated with severe recurrent bacterial pneumonia among children living with HIV. Methods: Children enrolled in the TREAT Asia Pediatric HIV Observational Database were included if they started antiretroviral therapy (ART) on or after January 1st, 2008. Factors associated with severe recurrent bacterial pneumonia were assessed using competing-risk regression. Results: A total of 3, 944 children were included in the analysis; 136 cases of severe recurrent bacterial pneumonia were reported at a rate of 6.5 [95% confidence interval (CI): 5.5–7.7] events per 1, 000 patient-years. Clinical factors associated with severe recurrent bacterial pneumonia were younger age [adjusted subdistribution hazard ratio (aHR): 4.4 for <5 years versus ≥10 years, 95% CI: 2.2–8.4, P < 0.001], lower weight-for-age z-score (aHR: 1.5 for <−3.0 versus >−2.0, 95% CI: 1.1–2.3, P = 0.024), pre-ART diagnosis of severe recurrent bacterial pneumonia (aHR: 4.0 versus no pre-ART diagnosis, 95% CI: 2.7−5.8, P < 0.001), past diagnosis of symptomatic lymphoid interstitial pneumonitis or chronic HIV-associated lung disease, including bronchiectasis (aHR: 4.8 versus no past diagnosis, 95% CI: 2.8−8.4, P < 0.001), low CD4% (aHR: 3.5 for <10% versus ≥25%, 95% CI: 1.9−6.4, P < 0.001) and detectable HIV viral load (aHR: 2.6 versus undetectable, 95% CI: 1.2−5.9, P = 0.018). Conclusions: Children <10-years-old and those with low weight-for-age, a history of respiratory illness, low CD4% or poorly controlled HIV are likely to gain the greatest benefit from targeted prevention and treatment programs to reduce the burden of bacterial pneumonia in children living with HIV.